Universitas Katolik di Indonesia dan Masalah Keutamaan Moral - Rodemeus Ristyantoro (Respons: Jurnal Etika Sosial, 2019)
ABSTRAK: Universitas adalah sebuah wadah pendidikan bagi manusia untuk mengembangkan diri. Namun, karena tuntutan pasar, perguruan tinggi dituntut untuk menjadi mesin pekerja. Artikel ini ingin mengetengahkan pentingnya pendidikan keutamaan dalam suasana pasar global dewasa ini. Dengan mengikuti pemikiran Aristoteles tentang keutamaan artikel ini menjawab permasalahan proses habitus dalam pendidikan keutamaan di perguruan tinggi Katolik. Artikel ini menyimpulkan bahwa keunggulan manusia masa depan amat ditentukan oleh proses pembiasaan yang dibangun di perguruan tinggi.KATA KUNCI: Pendidikan tinggi, nilai inti, budaya organisasi, keutamaan, etika Aristoteles.ABSTRACT: University is an educational institution for humans to develop themselves as humans. However, due to market demands, universities are required to becomeworkers’ machines. Th is article deals with the problem of the primacy of education in today’s global market atmosphere. By following Aristotle’s thoughts of virtues, this article explores that most of Catholic universities in Indonesia request the ethical habituation as the basic soft skill in its curricula. Th is article concludes that future human excellence is largely determined by the process of ethical habituation established in the higher education.KEYWORDS: Aristotle’s ethics, core values, higher education, organizational culture